Secondary level Students’ Lived Experience of Being Involved in Academic Writing in ELT Classroom - Basaula, Asmita (Ganeshman Darpan, 2024)
This paper explores and analyzes the grade eleven students’ lived experience of being involved in academic writing in ELT classroom. For this, I collected the required information taking phenomenological interview with the three purposively selected students of grade eleven from three respective institutional colleges of Nagarjun Municipality in Kathmandu. The collected information was thematically analyzed using ATLAS.ti 9. The lived experience of the secondary level students showed the inner and acquired threats of the students in researched context. The results reveal that both the inner and acquired threats of students have demotivated them to be involved in academic writing except the teacher’s supporting attitude which encouraged the students to improve their writing skill. Hence, the study concludes that there is need for using systematic strategies to motivate the students to be involved in academic writing supporting them to overcome the threats that they have been facing. Academic writing in ELT, making it even more appropriate and scientific for the betterment of overall teaching and learning of English in particular, and thereby the system of secondary level education as a whole.